Light-tree reconfiguration without flow interruption in sparse wavelength converter network. (3rd January 2022) - Atta, Amanvon Ferdinand; Cousin, Bernard; Adépo, Joël Christian; Oumtanaga, Souleymane
Network reconfiguration is an important task in WDM optical networks, which enables the optimisation of network resources. With the growing demand for multicast applications (e.g., distance learning, IPTV), this study focuses on the reconfiguration of the routing of a multicast connection. In this study, the path of the multicast connection is represented by a light-tree. A light-tree reconfiguration consists of migrating an optical flow from a light-tree to a new one. However, it is very difficult to automate light-tree reconfiguration without flow interruption. Flow interruption is undesirable for network operators. Therefore, the problem studied here is to find a sequence of operations in order to migrate an optical flow from a light-tree to a new one without flow interruption in a sparse wavelength converter network. For solving the light-tree reconfiguration problem, we propose a method based on a sub-tree approach. The comprehensive simulation results demonstrated the effectiveness of our method.